International consensus recommendations for the identification and treatment of tuberous sclerosis complex-associated neuropsychiatric disorders (TAND) - Petrus J. de Vries; Tosca-Marie Heunis; Stephanie Vanclooster; Nola Chambers; Stacey Bissell; Anna W. Byars; Jennifer Flinn; Tanjala T. Gipson; Agnies M. van Eeghen; Robert Waltereit; Jamie K. Capal; Sebastián Cukier; et al. (Journal of Neurodevelopmental Disorders, 2023)
Abstract Background Tuberous sclerosis complex (TSC) is associated with a wide range of physical manifestations for which international clinical recommendations for diagnosis and management have been established. TSC is, however, also associated with a wide range of TSC-Associated Neuropsychiatric Disorders (TAND) that are typically under-identified and under-treated yet associated with a profound burden of disease. The contemporary evidence base for the identification and treatment of TAND is much more limited and, to date, consensus recommendations for the diagnosis and management of TAND have also been limited and non-specific. Methods The TANDem project was launched with an international, interdisciplinary, and participatory consortium of 24 individuals, including TSC family representatives, from all World Health Organization (WHO) regions but one. One of the aims of the TANDem project was to generate consensus recommendations for the identification and treatment of TAND. At the time of this project, no internationally adopted standard methodology and methodological checklists existed for the generation of clinical practice recommendations. We therefore developed our own systematic procedure for evidence review and consensus-building to generate evidence-informed consensus recommendations of relevance to the global TSC community. Results At the heart of the consensus recommendations are ten core principles surrounded by cluster-specific recommendations for each of the seven natural TAND clusters identified in the literature (autism-like, dysregulated behavior, eat/sleep, mood/anxiety, neuropsychological, overactive/impulsive, and scholastic) and a set of wraparound psychosocial cluster recommendations. The overarching recommendation is to “screen” for TAND at least annually, to “act” using appropriate next steps for evaluation and treatment, and to “repeat” the process to ensure early identification and early intervention with the most appropriate biological, psychological, and social evidence-informed approaches to support individuals with TSC and their families. Conclusions The consensus recommendations should provide a systematic framework to approach the identification and treatment of TAND for health, educational, social care teams and families who live with TSC. To ensure global dissemination and implementation of these recommendations, partnerships with the international TSC community will be important. One of these steps will include the generation of a “TAND toolkit” of “what to seek” and “what to do” when difficulties are identified in TAND clusters.